FORMULATION AND EVALUATION OF HERBAL TABLETS USING CADAMBA (ANTHOCEPHALUS CADAMBA) - Abdul Hadi; Sadia Parveen; Jagriti Kumawat; Mahesh Kumar Posa; Saloni Goyal; Subhranshu Panda (The Bioscan, 2025)
The Cadamba is one of the important medicinal plants belonging to the Rubiaceae family. It is crucially significant as it has the largest number of phytochemicals and secondary metabolites having pharmacological and biological properties.It is extremely important since it contains the most phytochemicals and secondary metabolites with pharmacological and biological qualities, such as cadambagenic acid, cadamine, quinovic acid, β-sitosterol, cadambine, etc. It can be helpful in the development of different disease-curing and preventative medicines worldwide. The alchoholic and aqueous extract of this plant showed significant antibacterial and antifungal activity against almost all the organisms, Micrococcus luteus, Bacillus subtilis, Staphylococcus aureus, Escherichia coli etc. In this context, antimicrobial potential. A cadamba against a wide range of microorganisms was studied. To validate the ethnotherapeutic claims of the plant in skin diseases, wound healing activity was studied, besides antioxidant activity to understand the mechanism of wound healing.